Evaluation of the nutritional, sensory and microbial status of processed and preserved soft cheese types - Abdulhameed Abiodun Badmos; Kazeem Adeyemi; Afolabi Yusuff; Uthman Nabeel; Abdulrashid Yusuf; Helen Oyedepo; Samson Oyeyinka; Kafayat Belewu; Olusegun Lawal (Aceh Journal of Animal Science, 2021)
The high nutrient value and the high demand for cheese worldwide has necessitated the adoption of cheese alternatives including Soybean cheese, and different methods of processing it. This study was designed to determine the replacement value of these cheese types by comparing the nutritional, sensory, economic and bacterial attributes of differently processed cheese from cow milk and soybean (cow cheese and soya cheese respectively). Thirty samples each of cow cheese (boiled and fried) and soya cheese (boiled, fried, pepper-coated and egg-coated) constituted six treatments (T1 to T6). The cheese values and bacterial attribute of these six treatments were compared using a Completely Randomized Design. Results revealed that protein was highest in fried soya cheese, then the egg coated soya cheese, but lowest in the pepper coated soya cheese. The sensory values of egg coated soya cheese sample was highest. The pepper coated soya cheese had the highest content of tannins, isoflavones, steroids and phenols, while the fried cow milk cheese had the highest content of alkaloids and terpenoids. The pepper coated soyabean cheese (T5) had lowest bacterial count for the first two days of storage on the shelf. The fried cow cheese (T2) was also low in bacterial count, but highest in cost. The widely prevalent bacteria species in the cheese samples studied include Enterobacter aerogenes, Staphylococcus aureus and Lactobacillus plantarum. It was concluded that the freshly prepared cow cheese supplies calcium and sodium abundantly and is low in anti-nutritive factors, but the nutrients contained depreciates fast with storage while the highly nutritious and acceptable egg coated soya cheese and the phytochemicals-rich pepper coated soyabean cheese are highly recommended as lower cost cheese substitutes to enhance protein supply and bioavailability.